2018
DOI: 10.5194/hess-2017-715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical scales to explain urban hydrological response

Abstract: Abstract. Rainfall variability in space and time, in relation to catchment characteristics and model complexity, plays an important role in explaining the sensitivity of hydrological response in urban areas. In this work we present a new approach to classify rainfall variability in space and time and we use this classification to investigate rainfall aggregation effects on urban hydrological response. Nine rainfall events, measured with a Dual polarimetric X-Band radar at the CAESAR Site (Cabauw Experimental S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Durations of up to 3 h were chosen for the analysis, with multiple steps for min and h out of our interest for sub-hourly and sub-daily pattern. The values were not aggregated spatially, since this usually reduces the maximum intensity values (Cristiano et al, 2018).…”
Section: Data Processing and Quality Issuesmentioning
confidence: 99%
“…Durations of up to 3 h were chosen for the analysis, with multiple steps for min and h out of our interest for sub-hourly and sub-daily pattern. The values were not aggregated spatially, since this usually reduces the maximum intensity values (Cristiano et al, 2018).…”
Section: Data Processing and Quality Issuesmentioning
confidence: 99%
“…The performed calculations based on hydrodynamic models of urbanized and agricultural catchments [40][41][42] showed that convective rainfall events (short duration and high rainfall intensity) strongly affected drainage systems: flooding of manholes, reservoir overflows, stormwater overflows, etc. Thus, to limit these problems, proper decision-making during the control (or even the modernization) of existing stormwater networks is required.…”
Section: Introductionmentioning
confidence: 99%